Tecnologias de Informação e Comunicação em cidades inteligentes: o caso de Portugal - Nabais, Leonor (2021)
Smart cities are sustainable cities with people in mind, where social progress and well-being are the basis for the development of urban projects and solutions. Through the availability of Information and Communication Technologies and human capital, it is now possible to understand and improve the quality of life of citizens, thus being able to meet the needs of each individual, promoting their participation and providing a better monitoring what is happening in different cities. Therefore, it is important to verify which projects have been implemented in different cities in Portugal, which aim to achieve the principles of smart cities, in order to understand which path has already been built, and what remains to be done for make Portuguese cities smart cities. Tourism is becoming increasingly technological, so it is necessary to have the necessary tools to accompany it.